Aggregation-induced luminescence enhancement, anion sensing, solvent-selective fluorescence quenching of arylpyrazoline fluorescent probe. (February 2022) - Huang, Qiushuo; Liu, Tiantian; Ma, Danyang; Liu, Junxia; Ren, Tiegang; Wu, Wenpeng; Zhang, Jinglai
Abstract: 28 Novel pyrazoline compounds containing pyrazole units have been synthesized and characterized. The crystal structures of C 1 and B 6 showed that these pyrazoline derivatives could form 3D layered structures through face-to-face stacking of aromatic rings, and they were more inclined to form H-type aggregation in poor solvent. Compound C 4 was selected as the standard sample to study their properties of aggregation-induced emission enhancement (AIEE) and reversible mechanical chromoluminescence (MFC) behaviors in THF/cyclohexane. And the results suggested the formation of H-type aggregation, and the RIR and RIV phenomenon in the aggregated state led to strong fluorescence emission behavior in high fc solvent. The analysis of fluorescence emission spectroscopy indicated that the fluorescence emission of C 4 could be selectively quenched by chloroform. Meanwhile, compound C 4 can selectively recognize NO3 − in CH2 Cl2 . The studies of fluorescence quenching mechanism showed that compound C 4 could be oxidized by oxygen in the air to form a new compound C 4-1 in CHCl3 solvent or in the presence of NO3 −, leading to the fluorescence quenching of C 4 . Density functional theory calculations also confirmed the results. Highlights: A series of novel pyrazoline derivatives with aggregation-induced luminescence enhancement (AIEE) were designed and synthesized. The AIEE behavior and MFC behavior of compound C 4 were studied in detail. Compound C 4 has good selectivity to NO3 −, and could be applied to qualitative detection of NO3 − on test paper Strips. Compound C 4 had a certain solvent selectivity and showed obvious fluorescence quenching in chloroform.